Knowledge, attitude and practice of contraception by doctors and women in Kota Kinabalu, Sabah - Helen Benedict Lasimbang; Naing Oo Tha; Teo, John , Beng Ho; Lidwina Edwin Amir (2014)
Introduction: Over the past decade researchers have come up with reliable data to confirm the relationship between an increased availability of effective contraception and reduction in induced abortion rate. In Malaysia, the contraception prevalence rate according to the Malaysian Population and Family Survey in 1966 was 8.8 percent. It increased substantially to 36 percent in 1974 and further to 52 percent in 1984, but has leveled off since then to about 52% in 2004.lhe latest but unpublished data reported in 2014 showed 55%. The negative effect of this situation can be seen in the increasing report of babies 'abandonment, maternal mortality due to unsafe abortion and probably many other adverse effects associated with unintended pregnancy, although data on the latter is scarce. There is limited research on unmet contraceptive use in Sabah. The aim of this study is to determine the knowledge, attitudes and practices related to contraception among women and doctors. The findings of this study can provide k1eas for planning and implementing appropriate maternal health service delivery programs. Methods: This study uses descriptive as well as analytical community based cross sectional study. The clinics are selected using random systematic sampling method. A total of 240 women and 60 doctors were selected from either private or public clinic in Kota Kinabalu. The instrument used was face to face Interview and self-administered questionnaires for patients and doctors respectively. Statistical analysis was done using SPSS version 21. Results: Majority of the doctors (80%) felt that contraception is extremely important, and routinely discuss (63%) It with their patients. Oral contraceptive pill (97%) Is the most common type of contraceptive available in the doctor clinics. About 68% of doctors cited that abstinence plays a major part in their contraceptive advice. The average correct answer by doctors on knowledge is 62%. Almost an the women surveyed (98.8%) have heard of contraception from health professionals. Toe main reason for using is for spacing of pregnancy and many stops or did not use because of fear of side-effect. Women attending the public dink: appear to know more about female and male sterilization and intrauterine e011traceptive device compared to those attending private clinics. Conclusion: This study showed that both patients and doctors agreed the Importance r:I contraception. The low uptake of contraception appears to be due to concern of side-effects. It Is surprising to find out that 68% of doctors cited abstinence as major part of their contraceptive advice. The basic contraceptive knowledge of primary care doctors appears inadequate. Further and larger sample size Is needed to reinforce this study.